PEMANFAATAN SUP SAYUR LIMA UNSUR UNTUK MENJAGA KESEHATAN KELUARGA IBU â IBU PKK SEKIP RT . 06 / RW .VIII KELURAHAN KADIPIRO KECAMATAN BANJARSARI SURAKARTA - Endang Sri Sudalmi, JM. Sri Hardiatmi & (ADI WIDYA : JURNAL PENGABDIAN MASYARAKAT, 2017)
Sekip Kadipiro is a developing area with various income structure, especialy ini RT 06/RW 08. The people in this district, Just like the common society nowadays, get used to consume food added by sintetic addition spicies in which not good for the health particularly can damage important internal body organ. Beside that, the habit to consume over amount of nutrition can be trigers to various illness. These things are actually can be prevented by food management with balance nutritions which can be gained from various kind of vegetable. Hence, there is important to held training and workshop about the way to consume vegetable to maintain people health in this area. Training and workshop will give information about the benefits of each kind of vegetables, the way to get extract, and how to consume them properly. The information about 5 elements vegetable extract soup will help the people in this area to maintain their heatlh better. Those five elements are; beet , gobo, carrot, and shitake mushroom.Key words : Vegetable extract soup, beet , gobo, carrot, shitake mushroom, physical health.